2014
DOI: 10.1371/journal.pone.0096166
|View full text |Cite
|
Sign up to set email alerts
|

The Mucoid Switch in Pseudomonas aeruginosa Represses Quorum Sensing Systems and Leads to Complex Changes to Stationary Phase Virulence Factor Regulation

Abstract: The opportunistic pathogen Pseudomonas aeruginosa chronically infects the airways of Cystic Fibrosis (CF) patients during which it adapts and undergoes clonal expansion within the lung. It commonly acquires inactivating mutations of the anti-sigma factor MucA leading to a mucoid phenotype, caused by excessive production of the extracellular polysaccharide alginate that is associated with a decline in lung function. Alginate production is believed to be the key benefit of mucA mutations to the bacterium in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 61 publications
3
41
0
1
Order By: Relevance
“…Fluctuations in pyocyanin production in a series of 40 LES strains were reported, with overproduction during exacerbations in some CF patient strains and loss of pyocyanin during exacerbations in others (Fothergill et al, 2010). Downregulation of pyocyanin production was associated with a mucoid to non-mucoid switch (Ryall et al, 2014). Consistent with this, the mucoid strain IST 27 produced more pyocyanin relative to the spontaneous non-mucoid variant, IST 27N.…”
Section: Discussionmentioning
confidence: 67%
“…Fluctuations in pyocyanin production in a series of 40 LES strains were reported, with overproduction during exacerbations in some CF patient strains and loss of pyocyanin during exacerbations in others (Fothergill et al, 2010). Downregulation of pyocyanin production was associated with a mucoid to non-mucoid switch (Ryall et al, 2014). Consistent with this, the mucoid strain IST 27 produced more pyocyanin relative to the spontaneous non-mucoid variant, IST 27N.…”
Section: Discussionmentioning
confidence: 67%
“…In P. aeruginosa, this adaption occurs with a switch to the mucoid phenotype, characterized by overproduction of high-molecular-mass (Ͼ15-kDa) alginate exopolysaccharide (EPS) (7,8). This switch is accompanied by modification of acyl homoserine lactone (AHL)-and Pseudomonas quinolone signal (PQS)-dependent quorum-sensing (QS) systems (9), with altered production of virulence factors, e.g., pyocyanin and hydrogen cyanide (10). Extracellular alginate affords protection from host innate immune responses, including phagocytosis and neutrophil-derived reactive oxygen species (11).…”
mentioning
confidence: 99%
“…In this study, we show that alginate production alters the signalling response in P. aeruginosa PAO1 mucA22 strain. In a previous study, it was shown that both quinolone signalling and AHL signalling were repressed in the mucoid variant due to the low expression of QS genes (Ryall et al ., ). We further show that the alginate production itself influences the response to quinolone signals but not AHLs.…”
Section: Resultsmentioning
confidence: 97%
“…An equivalent amount of DMSO was added to control cultures. The pyocyanin assay was performed as described (Ryall et al ., ). The supernatant was collected by centrifugation.…”
Section: Methodsmentioning
confidence: 97%